LEGAL PROTECTION FOR FIXED-TERM EMPLOYMENT CONTRACT (PKWT) WORKERS IN OUTSOURCED COMPANY TRANSFERS FOLLOWING THE ENACTMENT OF INDONESIAN LAW NO. 6 OF 2023 - Liana, Liana; Rijadi, Prof. Dr. Prasetijo (jfpublisher, 2025)
This research seeks to elucidate the Job Creation Regulation Number 6 of 2023, promulgated on December 30, 2022, by the President of the Republic of Indonesia, as a manifestation of the Government's commitment to ensuring legal protection for citizens' rights to employment and a dignified standard of living through job creation. Employment relationships may arise due to labor, directives, and remuneration. This research examines the two primary forms of employment relationships recognized under Indonesian labor law: Fixed-Term Employment Agreements and Indefinite-Term Employment Agreements. It employs a statutory and conceptual approach as the methodological foundation. The research relies on various legal materials, which are systematically collected and analyzed to address the legal problems under investigation. This research aims to provide a precise, clear, and accurate comparison of Law Number 13 of 2023 concerning Employment and Job Creation Regulations (RI Law Number 6 of 2023 regarding the Enactment of Perpu Number 2 of 2022 on Job Creation). This approach reveals that workers under a Fixed-Term Employment Agreements (PKWT) receive legal protection and compensation from the outsourcing company following the termination of their work agreement, including in cases of transfer of the outsourcing company, as stipulated in the aforementioned regulation.